Level of urbanization and noncommunicable disease risk factors in Tamil Nadu, India - Steven Allender; Ben Lacey; Premila Webster; Mike Rayner; Mohan Deepa; Peter Scarborough; Carukshi Arambepola; Manjula Datta; Viswanathan Mohan (The World Health Organization, 2010)
OBJECTIVE: To investigate the poorly understood relationship between the process of urbanization and noncommunicable diseases (NCDs) through the application of a quantitative measure of urbanicity. METHODS: We constructed a measure of the urban environment for seven areas using a seven-item scale based on data from the Census of India 2001 to develop an "urbanicity" scale. The scale was used in conjunction with data collected from 3705 participants in the World Health Organization's 2003 STEPwise risk factor surveillance survey in Tamil Nadu, India, to analyse the relationship between the urban environment and major NCD risk factors. Linear and logistic regression models were constructed examining the relationship between urbanicity and chronic disease risk. FINDINGS: Among men, urbanicity was positively associated with smoking (odds ratio, OR: 3.54; 95% confidence interval, Cl: 2.4-5.1), body mass index (OR: 7.32; 95% Cl: 4.0-13.6), blood pressure (OR: 1.92; 95% Cl: 1.4-2.7) and low physical activity (OR: 3.26; 95% Cl: 2.5-4.3). Among women, urbanicity was positively associated with low physical activity (OR: 4.13; 95% Cl: 3.0-5.7) and high body mass index (OR: 6.48; 95% Cl: 4.6-9.2). In both sexes urbanicity was positively associated with the mean number of servings of fruit and vegetables consumed per day (P< 0.05). CONCLUSION: Urbanicity is associated with the prevalence of several NCD risk factors in Tamil Nadu, India.